KESIMPULAN DALAM PEMERIKSAAN KEPATUHAN YANG BERDIRI SENDIRI - Kariningsih, Catharina Sri; Asfaroyani, Nalini; Tutiana, Latifah Dewi (Badan Pemeriksa Keuangan Republik Indonesia, 2015)
BPK has the mandate to conduct audits over management and accountability of the state finance, with one of the audit types is Special Purpose Audit (PDTT). Based on the results of studies conducted by the Directorate of Research and Development of PDTT (Litbang PDTT) in 2011, PDTT consists of, among others, investigative and compliance audit. Compliance audit intended is a compliance audit performed independently. This study aims to provide information about the conclusions in the compliance audit which performed independently. The methodology used is literature study, audit reports analysis, data and information collection through questionnaires and interviews, as well as focus group discussions with practitioners and academician. Based on the study, it can be inferred that factors affecting the quality of the conclusion is the audit objective, the scope of the examination, criteria, materiality, sample and evidence. This study suggests to use ISSAI 4100 Compliance Audit Guidelines –For Audits Performed separately from the Audit of Financial Statements as a reference for the conclusion format.ABSTRAKBPK memiliki mandat untuk melakukan pemeriksaan atas pengelolaan dan tanggung jawab keuangan negara, diantaranya melalui Pemeriksaan Dengan Tujuan Tertentu (PDTT). Berdasarkan hasil kajian yang dilakukan Direktorat Litbang PDTT pada tahun 2011, pemeriksaan yang termasuk dalam PDTT adalah pemeriksaan investigatif dan kepatuhan. Pemeriksaan kepatuhan yang dimaksudkan adalah pemeriksaan kepatuhan yang berdiri sendiri. Tulisan ini bertujuan untuk memberikan informasi tentang penarikan kesimpulan dalam pemeriksaankepatuhan yang berdiri sendiri tersebut. Metodologi yang digunakan yaitu studi literatur, telaah LHP, pengumpulan data dan informasi melalui kuesioner dan wawancara, serta Focus Group Discussion dengan praktisi dan akademisi. Hasil studi menunjukkan bahwa faktor-faktor yang mendukung kualitas penarikan kesimpulan dalam pemeriksaan kepatuhan yang berdiri sendiri adalah tujuan, lingkup atau cakupan pemeriksaan, kriteria, materialitas, sampel dan bukti pemeriksaan. Studi ini mengusulkan bentuk kesimpulan yang mengacu pada ISSAI 4100 Compliance Audit Guidelines–For Audits Performed separately from the Audit of Financial Statements.